A trial to find appropriate animal models of dichloropropane‐induced cholangiocarcinoma based on the hepatic distribution of glutathione S‐transferases. Issue 6 (25th December 2015) - Zhang, Lingyi; Zong, Cai; Ichihara, Sahoko; Naito, Hisao; Toyokuni, Shinya; Kumagai, Shinji; Ichihara, Gaku
Abstract : A trial to find appropriate animal models of dichloropropane‐induced cholangiocarcinoma based on the hepatic distribution of glutathione Stransferases: Lingyi Zhang, et al . Department of Occupational and Environmental Health, Faculty of Pharmaceutical Sciences, Tokyo University of Science Objective: It has been reported that 1, 2‐Dichloropropane (DCP) induced cholangiocarcinoma (CCA) in offset color proof‐printing workers. However, exposure to DCP by inhalation or gavage for 2 year did not induce CCA in mice and rats. The present study mapped the hepatic distribution of GST, which is known to activate dihalogenated alkanes, and proliferative and fibrotic changes in bile ducts in various species to find the most appropriate animal model of DCP‐induced CCA. Methods: First, 12 each of C57BL/6J mice, Balb/cA mice, F344 rats, Syrian hamsters, and guinea pigs were divided into four equal groups and exposed to DCP at 0, 300, 1, 000, or 3, 000 ppm 8 hours/day for 7 days. Second, 32 Balb/cA mice and 32 Syrian hamsters were each divided into four equal groups and exposed to DCP at 0, 200, 400, and 800 ppm 6 hours/ day for 14 days. After the last exposure, the animals were decapitated, and the livers were dissected out for histopathological evaluation. Immunostaining was conducted to determine the distribution of GSTT1, GSTM1, and GSTPi, as well as the expression of proliferation marker Ki67. Results: GSTT1, GSTM1, and GSTPi were expressed in both hepatocytes and bile duct cells in all control and exposed animals. There was no clear difference in the expression of Ki67 between the exposed groups and the control. No fibrotic changes were observed in any species or strains examined. Conclusions: Expression of GSTT1 or other GST isozymes might not explain the difference in sensitivity of hepatocytes and the bile duct to DCP between humans and rodents